Endoscopic submucosal dissection for early gastric cancer: are expanded resection criteria safe for Western patients? - Probst, Andreas; Schneider, Annette; Schaller, Tina; Anthuber, Matthias; Ebigbo, Alanna; Messmann, Helmut (Endoscopy, 2017)
Background and study aims Endoscopic submucosal dissection (ESD) is the standard treatment for early gastric cancer (EGC) fulfilling guideline resection criteria or the expanded resection criteria in Asia. It is unclear whether the expanded criteria can be transferred to European patients, and long-term follow-up data are lacking. The aim of this study was to evaluate long-term follow-up data after ESD of EGCs in Europe.Patients and methods Patients with EGC who underwent ESD were included in this single-center study at a German referral center. Patient and lesion characteristics, procedure characteristics, and follow-up data were recorded prospectively.Results A total of 179 patients with 191 EGCs were included over a period of 141 months, with 29.6 % of lesions meeting guideline criteria and 48.6 % meeting expanded criteria. The en bloc resection rate was 98.4 % for guideline criteria and 89.0 % for expanded criteria lesions (P = 0.09), and the R0 resection rate was 90.2 % and 73.6 %, respectively (P = 0.02). The main reason for the expanded criteria was a lesion diameter > 20 mm (81.6 %). Complications: perforation 1 %, delayed bleeding 6.3 %, stricture 2.1 %, procedure-related mortality 1.1 %. Local recurrence rate was 0 % for guideline criteria and 4.8 % for expanded criteria lesions (P = 0.06), and the rate of metachronous neoplasia was 15.1 % and 7.1 %, respectively (median follow-up 51 and 56 months, respectively); 92.9 % of metachronous neoplasia were treated curatively with repeat ESD. One patient developed lymph node metastasis after ESD of a submucosal invasive expanded criteria lesion. Long-term-survival was comparable between the two criteria (P = 0.58). No gastric cancer-related death was observed in either group.Conclusions ESD can achieve high rates of long-term curative treatment using the expanded criteria in EGCs in Western countries. We recommend ESD as treatment of choice not only for guideline criteria EGCs but also for intramucosal nonulcerated EGCs regardless of their diameter.